Data Security Techniques Using Vigenere Cipher And Steganography Methods In Inserting Text Messages In Images - Smith, Vincent; Mendoza, Maximilian; Ullah, Insaf (Journal of Information Systems and Technology Research, 2024)
Improving data security has become a top priority in many industries, especially when it comes to sending and receiving private communications. Embedding text into photos using steganography and the Vigenere Cipher Method is one method of protecting text messages. In order to maintain the security of text embedded in images via web-based applications, the main challenge in this research is how to integrate and apply the Vigenere Cipher algorithm and LSB steganography while still paying attention to the size of the image message that has been ciphertexted. insertion and what not. Combining these two techniques aims to increase the level of security when encrypting message text. The message text is encrypted using the Vigenere Cipher to protect it; Encrypted messages are difficult to decipher without the right key. Meanwhile, message text may be hidden visually in photos using steganography. Text messages are efficiently disguised in images and significantly encrypted thanks to the combination of these two techniques. In this research, steganography and Vigenere Cipher techniques are used and tested on various types of images. The combined use of these two techniques effectively improves data security, according to test results. The study also discusses a number of possible defenses, such as image size and quality, that may arise from combining the two approaches. The findings of this research can be applied to improve the security of text messages in various contexts, such as online communications and data storage. Through the integration of steganography and Vigenere Cipher technology, users can guarantee the confidentiality of their communication texts and prevent unapproved access.